Workers' participation in OSH in Portugal - Marques Alves, P. (15th ESA Conference – Sociological Knowledges for Alternative Futures, 2021)
The available statistical information shows that accidents at work continue to have a strong incidence in Portugal, which makes this country one of the European states with one of the highest incidence rates in this field. Therefore, and notwithstanding the fact that matters related to OSH are legally regulated in detail, working continues to be an activity that involves numerous risks in Portugal, what happens in a context of a deep devaluation of work and of a growth in labour market deregulation. This situation calls for the need to deepen the joint action of the social partners, implying the indispensable participation of workers, which is legally foreseen, and which arises as a central issue of prevention strategies, as stated by Menéndez et al. (2008: 5) Participation can take place in two ways. The first is by the collective bargaining. The second is the election of health and safety representatives and their participation in specialised OSH committees. With this paper we intend to make a review of the election of health and safety representatives since 2004, as well as to assess the regulation of OHS in collective bargaining in the last three years. We will highlight the scarce number of elections held, and that in the collective bargaining the contents negotiated are in general quite generic and follow strictly the legislation, although some provisions stand out. We conclude by stating that the Portuguese unions have not been able to obtain new rights in this field beyond those enshrined in the legislation.